Comprehensive Genomic Profiling of Indian Patients With Lung Cancer - Shivani Sharma; Vanita Noronha; Arti Yadav; Madhvi Mandhania; Sambit K. Mohanty; Rahul Katara; Aditi Aggarwal; Sagar Samrat Mohanty; Akash Kumar; Sanjeev Kumar; Vipin Kumar; Kanika Jaggi; et al. (JCO Global Oncology)
PURPOSEGenomic profiling has revolutionized non–small cell lung cancer (NSCLC) therapy, but molecular data on Indian patients with NSCLC are limited.MATERIALS AND METHODSWe analyzed next-generation sequencing (NGS) data of 5,219 Indian patients with lung cancer, tested between May 2022 and August 2023 at CORE Diagnostics, a commercial laboratory in India. Using the PulmoCORE gene panel, we targeted 13 key genes (ALK, BRAF, EGFR, ERBB2, KRAS, MAP2K1, MET, NRAS, PIK3CA, RET, ROS1, TP53, and NTRK) for DNA and RNA sequencing. PD-L1 was tested by immunohistochemistry.RESULTSMedian patient age was 62 years, and 62.5% were male. Common histologies included adenocarcinoma (57.1%), NSCLC not otherwise specified (19.3%), and squamous cell carcinoma (7%). Genomic alterations were detected in 80.6% patients according to the PulmoCORE panel; 64.2% patients had actionable alterations in at least one of the nine biomarkers with Food and Drug Administration–approved targeted therapies, that is, EGFR, KRAS, ALK, ROS1, BRAF, NTRK1/2/3, MET, RET, and ERBB2. Common alterations included TP53 (37%), EGFR (34.1%), and KRAS (13.3%), ALK (8.8%), and others below 5%. Alterations were more common in adenocarcinoma (76.4%) than in patients with squamous cell carcinoma (29.9%). Sex and age influenced mutation prevalence, with EGFR mutations more common in females and KRAS in males, while ALK, ROS1, and RET fusions were prevalent in younger adults. Most genomic alterations were mutually exclusive, although 25% patients had co-occurring mutations. PD-L1 positivity was higher in males (28.3%) and more common in patients with squamous cell carcinoma (34.2%).CONCLUSIONBroad molecular profiling is important to detect actionable alterations in Indian patients with lung cancer, for delivering optimal personalized precision medicine. Our study underscores the fact that NGS should be routinely done before planning therapy in Indian patients with advanced lung cancer.